People and the Place: Social Dominance Orientation Is Reciprocally Associated With Hierarchy-Enhancing Occupations Over Time. (May 2022) - Zubielevitch, Elena; Cheung, Gordon W.; Sibley, Chris G.; Sengupta, Nikhil; Osborne, Danny
Social dominance orientation (SDO) is a widely researched construct that indexes a preference for hierarchical intergroup relations. However, it remains unclear whether this preference (a) motivates people to seek out occupations that enhance hierarchical relations between groups (i.e., occupational assortment), (b) develops as a result of working within hierarchy-enhancing occupations (i.e., occupational socialization), or (c) both. One reason for this gap is that the large-scale longitudinal data required to simultaneously model assortment and socialization processes are scarce. In this study, we analyzed data from two waves of longitudinal data (spaced either 1, 3, or 5 years apart) from a nationwide sample of adults ( N = 3, 452–4, 412) who were already working in either hierarchy-enhancing occupations (e.g., law enforcement) or hierarchy-attenuating occupations (e.g., social work). Results showed that SDO predicted an increased probability of working in a hierarchy-enhancing occupation 3 and 5 years later. Working in a hierarchy-enhancing occupation was also positively associated with SDO after 1 and 5 years. These patterns generally suggest that occupations both shape, and are shaped by, intergroup beliefs.